Virucidal efficacy of a sonicated hydrogen peroxide system (trophon EPR) following European and German test methods - Becker, Britta; Bischoff, Birte; Brill, Florian H. H.; Steinmann, Eike; Steinmann, Jochen (German Medical Science GMS Publishing House, 2017)
Aim: The virucidal efficacy of an automated ultrasound probe disinfector (trophon EPR) was evaluated in a three step procedure according to European and German test methods. This system uses sonicated hydrogen peroxide mist (35%) at elevated temperature (50°C) in a closed chamber with control of all parameters within a 7 minute cycle. Methods: In the first step of examination, the peroxide solution was tested in a quantitative suspension assay according to the Guideline of Deutsche Vereinigung zur Bekämpfung der Viruskrankheiten (DVV) e.V. and Robert Koch-Institute (RKI) and in parallel with the European Norm EN 14476 with all test viruses creating a virucidal claim. In the second step, the virucidal efficacy of the hydrogen peroxide solution was evaluated in a hard surface carrier test according to the Guideline of DVV with adenovirus, murine norovirus and parvovirus simulating practical conditions. Finally, the efficacy was evaluated by the automated system using stainless steel carriers inoculated with test virus and positioned at different levels inside the chamber. Results: A ≥4 log reduction of virus titre was demonstrated with all methods including carrier tests with murine norovirus, adenovirus, and parvovirus using the automated device. Conclusion: The automated device is able to inactivate test viruses of German and European norms and can therefore claim efficacy against human pathogenic enveloped and non-enveloped viruses. This includes human papillomaviruses which form part of the complete virucidal claim.